A giant extra-uterine fibroma originating from an utero-ovarian ligament initially diagnosed as an ovarian tumour [Over tümörü olarak öntanısı konulan utero-ovaryen ligamentten kaynaklanan dev ekstra-uterin fibrom] - (:unkn) unknown (Marmara University, 2014)
A 44-year-old virgin with abdominal mass and anemia was admitted to our hospital. The patient complained of constipation and a palpable mass in the abdomen for about 4 years. On transabdominal ultrasonography, a giant, complex, solid, lobulated mass 152x142x81mm in size was observed. Exploratory laparotomy was performed. There was a giant, multiple lobulated irregular-shaped solid mass occupying the whole abdomen, reaching the xiphioid and infiltrating the omentum. The size of the mass arising from the left utero-ovarian ligament was approximately 30x15cm. The histopathologic report confirmed the diagnosis of leiomyoma with myxoid degeneration. © 2014, Marmara University. All rights reserved.
Keywords: Adnexial tumor; Fibroma; Leiomyoma; Ovarian mass